AN AUTO-ETHNOGRAPHY REFLECTION ON WEAWING: A PHILOSOPHICAL ACCOUNT OF LIVED EXPERIENCES - Apau, Edward (ARTISTIC : International Journal of Creation and Innovation, 2025)
Hand-weaving is often perceived as time-consuming and tedious due to its labour-intensive preparatory processes, leading to declining interest in the practice. However, weaving offers insights that extend beyond technical execution, providing profound opportunities for philosophical reflection and self-realisation. This auto-ethnographic, studio-based study explores weaving as a metaphor for human experience, drawing connections between the preparatory stages of weaving and the shaping of personal growth. The findings reveal that hand-weaving transcends the physical interlacement of warp and weft, embodying a process of self-development, resilience, and reflective practice. While acknowledging the challenges associated with manual weaving, the study argues for its continued relevance, not merely as a fabric manufacturing technique, but as a medium for cultivating self-awareness and creativity. It recommends that weaving education should emphasise experiential engagement and self-discovery, rather than focusing solely on technical proficiency or theoretical instruction